The Determination of Heavy Metals (Cd and Pb) in Bivalve Molluscs Commercial Interest Four Estuaries of the Gulf of Guayaquil (Revista Científica Ciencias Naturales y Ambientales, 2010)
In the present work two species of bivalve molluscs (Mytella strigata and Ostrea columbiensis) of great importance both for trade and domestic consumption in the communities located in the Gulf of Guayaquil were used in order to establish a baselineconcentration of cadmium and lead found in these organisms and confirm their relevance as bioindicators of pollution by these metals. Within the framework of the study the highest concentration of lead was found in oysters from the Las Cruces estuary with 5.03 ppm / dry weight, followed by oysters from Chupadores Chico estuary with 1.96 ppm / dry weight. In the Chupadores Grande and Las Loras estuaries, the highest concentrations of lead were found in mussels and 1.98 and 1.75 ppm / dry weight, respectively. The values recorded in ppm dry weight were transformed into wet weight for comparison with the maximum permitted by the European Commission (2006). The concentrations of cadmium and lead were within the permissible limits of the Ecuadorian legislation in the four estuaries sampled, however in the sediment differences between the concentrations of these elements were found, in the case of cadmium the values ranging from 0.82 to 1.82 ppm / dry weight and lead values from 8.35 to l1.55 ppm / dry weight.
Keywords: Cadmium; lead; oysters; mussels.